Phonetic Segments and the Organization of Speech. - Gasparri, Luca (Philosophy of Science, 2019)
According to mainstream linguistic phonetics, speech can be modeled as a string of discrete sound segments or "phones" drawn from a universal phonetic inventory. Recent work has argued that a mature phonetics should refrain from theorizing about speech and speech processing using sound segments and that the phone concept should be eliminated from linguistic theory. The article lays out the tenets of the phone methodology and evaluates its prospects in light of the eliminativist arguments. I claim that the eliminativist arguments fail to show that the phone concept should be eliminated from linguistic theory.